2017
DOI: 10.1021/acs.jproteome.7b00381
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Chain Enrichment Middle-Down Mass Spectrometry (UbiChEM-MS) Reveals Cell-Cycle Dependent Formation of Lys11/Lys48 Branched Ubiquitin Chains

Abstract: The dynamics of cellular signaling events are tightly regulated by a diverse set of ubiquitin chains. Recent work has suggested that branched ubiquitin chains composed of Lys11 and Lys48 isopeptide linkages play a critical role in regulating cell cycle progression. Yet, endogenous Lys11/Lys48 branched chains could not be detected. By combining a Lys11 linkage specific antibody with high-resolution middle-down mass spectrometry (an approach termed UbiChEM-MS) we sought to identify endogenous Lys11/Lys48 branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…We direct readers to recent reviews that cover broader technologies for analysis of phosphorylation, 102 104 glycosylation, 105 107 and PTMs in general 100 , 101 for further insights. We also note that ETD has been valuable for PTM analysis beyond the scope discussed here, including ubiquitylation, 108 110 ADP-ribosylation, 111 113 and arginine methylation. 114 118 …”
Section: Characterizing Post-translational Modifications With Etdmentioning
confidence: 97%
“…We direct readers to recent reviews that cover broader technologies for analysis of phosphorylation, 102 104 glycosylation, 105 107 and PTMs in general 100 , 101 for further insights. We also note that ETD has been valuable for PTM analysis beyond the scope discussed here, including ubiquitylation, 108 110 ADP-ribosylation, 111 113 and arginine methylation. 114 118 …”
Section: Characterizing Post-translational Modifications With Etdmentioning
confidence: 97%
“…Notably, UBE2S assembles non-canonical ubiquitin chains, linked through K11 in ubiquitin [3841]. In addition, more recent evidence points to an ability of APC/C to form branched or heterotypic chains, and these unique chain topologies could provide strong signals for organizing the temporal ordering of substrate degradation at mitotic exit [4244].…”
Section: Apc/c Structure and Functionmentioning
confidence: 99%
“…PR-619 has become a useful tool in order to probe the role of ubiquitination in various cell biologic systems (Balut et al, 2011; Seiberlich et al, 2012; Pandey and Kumar, 2015; Crowder et al, 2016; Rana et al, 2017; Wang et al, 2017); however, the work here suggests that some caution should be applied when using this inhibitor in cell line–based studies. We have observed that at concentrations 20 µ M and above, PR-619 induces TOP2-covalent DNA complexes in K562 cells that are converted to DNA double-strand breaks.…”
Section: Discussionmentioning
confidence: 95%
“…In cell-based assays PR-619 was shown to substantially inhibit the activity of ubiquitin-specific protease, ubiquitin carboxy-terminal hydrolase, OTU, and MJD class DUBs when applied at 20–50 µ M, and exhibited a clear effect at a concentration as low as 5 µ M (Altun et al, 2011). PR-619 has been employed as a tool to investigate the role of ubiquitination in cellular processes including lysosomal degradation (Balut et al, 2011), caspase activation (Crowder et al, 2016), the stability of sirtuin-7 (Pandey and Kumar, 2015), protein aggregate formation (Seiberlich et al, 2012), human immunodeficiency virus replication (Setz et al, 2017), and oocyte maturation (Wang et al, 2017), as well as in the analysis of ubiquitin chain structure (Rana et al, 2017). In addition, PR-619 also inhibited the de-SUMOylating enzyme sentrin-specific protease (SENP) 6 in vitro and leads to accumulation of SUMOylated proteins in cells (Altun et al, 2011; Barry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%